INNOVATIVE AC-DC POWER SUPPLY: A VERSATILE DUAL-MODE APPROACH TO LOCALIZED SUSTAINABLE ENERGY SOLUTION - Cortez, Angelica O (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
In developing countries like the Philippines, outages of electricity supply in countryside are common caused by calamities resulting to isolation, thus, affecting the quality of life and delivery of instruction in the affected area. The developed Innovative AC-DC Power Supply Dual-Mode Distribution (ICPS-DMD) is a device created through product developmental research to provide a localized sustainable energy solution for isolated community households and schools in the mountainous Sitio Cabog in Dingalan, Aurora where the university adopted school is located. Validated assessment instruments with Cronbach Alpha = 0.94 were developed and utilized. Licensed electrical engineers employed in the university as experts assessed its design, materials used, and safety while local classroom teachers and parents, assessed the ICPS-DMD for functionality, usability, and safety. Data were analyzed employing one-tailed t-test for independent variables, One-way ANOVA and PostHoc Analysis for Multiple Comparison using SPSS v. 20. The ICPS-DMD facilitates and controls the direct use and safe utilization of 12Vdc electricity supply from a car battery and its conversion to 220Vac to provide electricity for household gadgets, appliances and instructional devices. Test results confirmed that the design and materials used to develop ICPS-DMD passed the assessment of experts with F-test = 2.233 and PostHoc analysis revealed no significant differences on the results. Said device was rated very functional, very useful, and very safe by the respondents with t-test=-1.80 in providing localized electricity supply for both 12Vdc and 220Vac powered devices. The device received patent recognition from the Intellectual Property Office of the Philippines.